2013
DOI: 10.1002/pds.3526
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adherence in long‐term use of statins

Abstract: Poor adherence in long-term use of statins is commonplace, but a number of key predictors-including age, language other than English spoken at home, smoking status and psychological distress-are readily assessable by the prescribing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
50
3
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 41 publications
10
50
3
3
Order By: Relevance
“…16 Also, obesity has been linked with good adherence to statin therapy. 10,14 However, results have been inconsistent, with some studies showing no association between adherence and obesity 12,17 or physical activity, 12,14 or even an association between adherence to statins and smoking history. 17 Furthermore, few studies have provided information on the association between lifestyle factors and statin adherence stratified by cardiovascular comorbidity, which may modify these associations.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…16 Also, obesity has been linked with good adherence to statin therapy. 10,14 However, results have been inconsistent, with some studies showing no association between adherence and obesity 12,17 or physical activity, 12,14 or even an association between adherence to statins and smoking history. 17 Furthermore, few studies have provided information on the association between lifestyle factors and statin adherence stratified by cardiovascular comorbidity, which may modify these associations.…”
mentioning
confidence: 97%
“…3−5 Patients who adhere to preventive drug treatment are often assumed to also have an otherwise healthier lifestyle than those with poor adherence. 6−8 Accordingly, some studies have found current smoking status 9−14 and high alcohol consumption 14,15 to be associated with nonadherence to lipid-lowering therapy. In a Canadian study involving patients in primary care practices, those who reported regular exercise or a healthy diet had high scores of self-reported statin adherence.…”
mentioning
confidence: 99%
“…These data have been used extensively for health services and pharmacoepidemiological studies 20, 21…”
Section: Methodsmentioning
confidence: 99%
“…There was no correlation with income or with the place of residence. 23 Despite the availability of statins in the pharmacy of the health institution, the drug was bought from commercial pharmacies by 83 (23.9%) of the 347 respondents, and bought as complement in the primary SUS network by 70 respondents (20.2%).…”
Section: Caregiver Supportmentioning
confidence: 99%